Experimental evaluation of interaction design in virtual reality - Marshall, Eleanor (2005)
Desktop Virtual Reality (VR) is a simple and affordable way to implement VR technology into an organisation. With PC technology developing at a phenomenal pace fast processor speeds enable the relatively easy development of visually impressive Virtual Environments (VEs) that can be used with familiar desktop PCs for novice and expert end users alike. A need had consequently evolved to ensure that VE development is structured so that VEs can be visually impressive, usable and effective for their purpose. Interaction between the user and the VE is a distinguishing feature of VR but the importance of interaction on the effectiveness of the VE has been little explored, in particular how to measure that effectiveness with a view to providing guidance to VE developers in this case for training applications using the familiar and affordable desktop medium. The use of VR as a training tool has been widely investigated and implemented in both research and industry.